Three-year outcomes after kyphoplasty in patients with osteoporosis with painful vertebral fractures - Kasperk, Christian; Grafe, Ingo Alexander; Schmitt, Sven; Nöldge, Gerd; Weiß, Christel; Da Fonseca, Katharina E.; Hillmeier, Joachim S.; Libicher, Martin; Sommer, Ulrike; Rudofsky, Gottfried; Meeder, Peter-Jürgen; Nawroth, Peter Paul (Journal of vascular and interventional radiology, 2010)
Kyphoplasty immediately improves pain and mobility in patients with painful osteoporotic vertebral fractures, but long-term clinical outcomes are still unclear. This controlled trial evaluates pain, mobility and fracture incidence 3 years after kyphoplasty.